Reliability analysis of rice milling station via Gumbel Hougaard Family Copula. (19th June 2023) - Usman, Nafisatu Muhammad; Yusuf, Ibrahim
This paper presents the availability modelling and performance analysis of a linear consecutive k-out-of-n system of the milling section of a rice mill plant consisting of four subsystems, namely cleaning and destoning section, husking and paddy separation section, rice grading and polishing section and lastly sorting and bagging section. During operation, the system undergoes two possible states of operation namely, full capacity and failed state. Using Gumbel-Hougaard Family Copula, the state probabilities for the proposed schemes are obtained and system availability, reliability and MTTF are calculated. Numerical examples are presented to illustrate the results obtained and to analyse the effect of different system parameters. The finding of this paper will boost the efficiency of the system and will be useful for timely maintenance progress, decision-making, preparation and optimisation. Through Laplace transforms using regenerative point techniques, the first-order system of differential equations was formulated from the transition diagram and solved. Maple 18 software was used to perform the numerical computations. The performance of the system was assessed through the numerical results obtained.